A Randomized Trial of Split Dose 3 L Polyethylene Glycol Lavage Solution, 2 L Polyethylene Glycol Lavage Combined With Castor Oil, and 1 L of Polyethylene Glycol Lavage Solution Combined With Castor Oil and Ascorbic Acid for Preparation for Colonoscopy - Tian, Xu; Shi, Bing; Liu, Xiao-Ling; Chen, Hui; Chen, Wei-Qing (Frontiers in Medicine, 2019)
Background: Castor oil has the potential of halving the required volume of bowel preparation solution; however no clinical trial investigated the efficacy of castor oil on bowel preparation for colonoscopy in addition to polyethylene glycol (PEG). Objectives: Our aim was to evaluate efficacy and safety of 30mL CaO alone or plus Asc in bowel preparation before colonoscopy. Methods: Two hundred and forty six patients were allocated randomly to ingest 2L PEG with 30mL CaO, 1L PEG with 30mL CaO plus 5g Asc, or 3L PEG. We used Boston Bowel Preparation Scale (BBPS) to evaluate bowel preparation efficacy. We also determined other outcomes such as procedure time, polyp or adenoma detection rate and adverse events (AEs). Results: Of 282 patients recruited, 36 were excluded. Groups were matched for baseline characteristics except weight (P = 0.020) and body mass index (BMI) (P = 0.003). Patient’s satisfaction were higher in 2L PEG-CaO (P = 0.016) and 1L PEG-CaO-Asc groups (P = 0·017). Patients’ compliance was 67.5%, 71.4% and 80.5% in 3L PEG, 2L PEG-CaO and 1L PEG-CaO-Asc groups (P = 0.014). Adequate bowel preparation rate was 75%, 78.57% and 53.66% in 3L PEG, 2L PEG-CaO and 1L PEG-CaO-Asc groups (P = 0.021). There were no differences in terms of remaining outcomes. Conclusions: Despite an increase in patients’ satisfaction and compliance, 1L PEG-CaO-Asc significantly decreased adequate bowel preparation rate. However, 2L PEG-CaO improved the patients' satisfaction and compliance and increased adequate bowel preparation rate.